EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN BUAH-BUAHAN DI DESA CUKILAN, KECAMATAN SURUH, KABUPATEN SEMARANG - Oktaviana Karmia Krisanti; Andree Wijaya Setiawan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Cukilan Village has a land area of 702.8 ha, with land use for agriculture covering an area of 620.2 ha. Agricultural land is widely used for fruit crops such as durian, rambutan and mango, but the production is considered not optimal, so it is necessary to evaluate the suitability of the land. This research was conducted to determine the characteristics of the Cukilan Village land; land suitability class for durian, rambutan and mango commodities; as well as land limiting factors. The research was carried out for 5 months and referred to the Technical Manual for Evaluation of Land Suitability for Agricultural Commodities with modifications to the determination of land suitability classes and limiting factors. The results of this study indicate that the land suitability class for durian and rambutan is moderately suitable (S2) with an area of 606.4 ha (97.8%) and marginally suitable (S3) with an area of 13.8 ha (2.2%). Land suitability class for mangoes is moderately suitable (S2). The limiting factors for durian, rambutan, and mango plants were rainfall, slope, drainage, KB, CEC, pH, and C-organic. Actions that can be taken to increase the productivity of these commodities are adding suitable organic matter, soil ameliorants such as lime and other materials containing CaCO3 and MgO3 and carrying out land management.